THE INFLUENCE OF AUDIT COMPETENCE AND AUDITOR PERFORMANCE ON AUDIT QUALITY ACCORDING TO AUDITOR'S PERCEPTION - Adela; Amelia Setiawan; Hamfri Djajadikerta (Journal of Social and Economics Research, 2024)
This study examines the impact of audit competence and auditor performance on audit quality. Auditors are individuals who conduct audits, which are systematic processes to obtain and evaluate objective evidence related to the financial reports of entities such as companies, organizations, or government agencies. Audit competence includes sufficient knowledge and experience to conduct audits objectively and meticulously. Auditor performance, encompassing work quality, timeliness, and error rates, also plays a significant role in determining audit quality. This study aims to determine whether audit competence and auditor performance individually and collectively affect audit quality. The results of this research are expected to provide benefits to Public Accounting Firms (PAFs), auditors, and future research by offering insights into the importance of competence and performance in producing high-quality audits.